Molecular subtypes, prognostic factors, and treatment optimization in pediatric medulloblastoma: a real-world study from China - Liu, Jingjing; Sun, Yanling; Li, Huming; Du, Shuxu; Zhang, Jin; Zhang, Zhen; Sun, Liming; Wu, Wanshui (Frontiers in Oncology, 2025)
BackgroundMedulloblastoma (MB) is the most common malignant pediatric brain tumor, yet systematic studies on molecular characteristics and treatment efficacy in Chinese pediatric MB remain scarce. This study evaluates recurrence and mortality risk factors and the feasibility of intensified chemotherapy.MethodsA retrospective analysis of 381 MB patients (WNT: 63, SHH: 106, Group 3: 27, Group 4: 185) was conducted. Kaplan-Meier analysis estimated survival rates, and Cox regression identified independent risk factors for recurrence and mortality.ResultsWith a median follow-up of 4.8 years, 5-year PFS and OS were 69.9% ± 2.4% and 80.6% ± 2.1%, respectively. WNT-MB had the best prognosis, while Group 3-MB had the worst. Independent recurrence risk factors included high-risk status (HR=2.931, p<0.001), TP53 mutation (HR=1.873, p<0.001), MYCN amplification (HR=1.52, p=0.001), chromosome 12p amplification, and 9q deletion. Mortality was associated with LC/A pathology (HR=1.573, p=0.007), TP53 mutation (HR=2.049, p<0.001), and high-risk status (HR=3.966, p<0.001). TP53 mutations influenced WNT-MB recurrence, and Group 3-MB showed a high recurrence risk even without MYC amplification or metastasis. No treatment-related fatalities were observed.ConclusionThis study identified key clinical and molecular risk factors associated with recurrence and mortality in pediatric medulloblastoma. The findings underscore the prognostic relevance of TP53 mutations, MYCN amplification, and specific chromosomal alterations, particularly in non-metastatic subgroups. These insights may help guide risk-adapted and personalized treatment strategies in future studies.